2004
DOI: 10.1111/j.0906-6705.2004.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

TARC augments TNF‐α‐induced CTACK production in keratinocytes

Abstract: Thymus- and activation-regulated chemokine (TARC)/CCL17 and cutaneous T cell-attracting chemokine (CTACK)/CCL27 are both pivotal mediators of the inflammatory reaction of atopic dermatitis (AD). TARC attracts CCR4 positive T cells known to be mainly of Th2 subtype whereas CTACK attracts skin-homing T cells of both Th1 and Th2 subtype that express CCR10. We found that CTACK can be induced in cultured human keratinocytes by tumor necrosis factor-alpha (TNF-alpha), but not by TARC alone. However, if the keratinoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…A recent report revealed that TARC/CCL17, a ligand for CCR4, is significantly elevated in MF patients' serum, and that this is correlated with clinical and disease stages (19). It is also reported that TARC/CCL17 augments CTACK/CCL27 expression through tumor necrosis factor-a in atopic skin (20). These findings account for our observations that serum CTACK/CCL27 levels are elevated in patients with MF in accordance with the advance of the clinical stage.…”
Section: Discussionsupporting
confidence: 87%
“…A recent report revealed that TARC/CCL17, a ligand for CCR4, is significantly elevated in MF patients' serum, and that this is correlated with clinical and disease stages (19). It is also reported that TARC/CCL17 augments CTACK/CCL27 expression through tumor necrosis factor-a in atopic skin (20). These findings account for our observations that serum CTACK/CCL27 levels are elevated in patients with MF in accordance with the advance of the clinical stage.…”
Section: Discussionsupporting
confidence: 87%
“…Cells were treated with various concentrations of RuCO as exogenous CO donor for 30 min and then with and without IFN-γ (10 ng/mL) and TNF-α (10 ng/mL) for 9 h. Total RNAs were extracted and chemokines expression were subjected for RT-PCR analysis. (Vestergaard et al, 2000(Vestergaard et al, , 2004. Recently, Frukawa et al (2004) also reported that PBMC from atopic dermatitis patients produces TARC/CCL17 in response to dust-mite allergens, which are well-known environmental allergens.…”
Section: Discussionmentioning
confidence: 99%
“…CTACK/CCL27 also is highly expressed in the basal epidermis of lesioned skin of NC/ Nga mice, which are regarded to be a mouse model of human AD, and CTACK/CCL27 expression in the basal epidermis disappears as the lesion heals (Vestergaard et al, 1999). Furthermore, Vestergaard et al (2000Vestergaard et al ( , 2004 reported that CATCK/CCL27 is expressed in HaCaT cells when the cells are stimulated with TNF-α and was a major regulator of keratinocyte precursor cell migration from the bone marrow to the skin. CTACK/CCL27 is pivotal in mediating the migration of CLA + lymphocytes into the skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF is a major proinflammatory cytokine that is thought to be important in the pathogenesis of asthma [12], food allergy [13,14], ocular allergy [15], and atopic dermatitis [16]. It has been reported that increased number of TNF expressing cells and levels of TNF are observed in the bronchoalveolar lavage (BAL) and in the airways of asthmatics [17], respectively.…”
Section: Introductionmentioning
confidence: 99%